2005
DOI: 10.1007/s10585-005-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

An Orthotopic Model of Human Osteosarcoma Growth and Spontaneous Pulmonary Metastasis

Abstract: Osteosarcoma is the most common primary malignancy of bone and patients often develop pulmonary metastases. In order to investigate the pathogenesis of human osteosarcoma, there is a great need to develop a clinically relevant animal model. Here we report the development of an osteosarcoma animal model using three related human osteosarcoma lines, the parental TE-85 and two derivative lines MNNG/HOS and 143B. In vitro characterization demonstrated that the 143B line had the greatest cell migration and the leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
234
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(247 citation statements)
references
References 51 publications
13
234
0
Order By: Relevance
“…To assure that this finding is not specific to only the MG63-derived sublines, we examined IGFBP5 expression in two other commonly used OS cell lines (143B and MNNG/HOS) that are not related to the MG63 lines (Figure 2b). We have previously shown that the 143B line is significantly more metastatic compared with the MNNG/HOS line (Luu et al, 2005a;Su et al, 2009). IGFBP5 mRNA and protein expression was detectable among the lines, with MNNG/HOS demonstrating the higher expression compared with the highly metastatic 143B line.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…To assure that this finding is not specific to only the MG63-derived sublines, we examined IGFBP5 expression in two other commonly used OS cell lines (143B and MNNG/HOS) that are not related to the MG63 lines (Figure 2b). We have previously shown that the 143B line is significantly more metastatic compared with the MNNG/HOS line (Luu et al, 2005a;Su et al, 2009). IGFBP5 mRNA and protein expression was detectable among the lines, with MNNG/HOS demonstrating the higher expression compared with the highly metastatic 143B line.…”
Section: Resultsmentioning
confidence: 86%
“…We next sought to investigate IGFBP5's role on primary tumor growth in our orthotopic animal model, using the MG63.2 and 143B cell lines that we have previously characterized (Luu et al, 2005a;Su et al, 2009). Cells were equally infected with adenovirus expressing RFP only (AdRFP), AdR-IGFBP5 or AdR-siIGFBP before subperiosteal implantation.…”
Section: Igfbp5 Inhibits Primary Tumor Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,2) MNNG cells are one of several recently characterized OS cell lines that mimic human OS when orthotopically xenografted into nude mice. (38) MNNG cells also express a truncated, constitutively activated version of Met, (26,27) making the MNNG cell line an appropriate model for testing the in vivo effects of PF-2341066 on OS growth. When xenografted into the proximal tibias of nude mice, MNNG cells produced rapidly growing tumors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4) suggest that this may in fact be the case, MNNG cells have a relatively low frequency of pulmonary metastasis when injected into mouse tibias. (38) We therefore plan to test the ability of PF-2341066 to inhibit the growth of MNNG cells in lungs when xenografted via tail-vein injection. Of note, another Met inhibitor, PF-04217903, was reported recently to inhibit the pulmonary growth of OS cells xenografted using this method.…”
Section: Discussionmentioning
confidence: 99%